Role of enzymes in initiating sexual cycle in different species of Morchella - and MUGDHA TIWARI, SHWET KAMAL, S.K. SINGH (Indian Phytopathology, 2004)
The variation in production of C1 cellulase, Cx cellulase, Xylanase, ÃŸ-glucosidase, laccase, polyphenol oxidase and peroxidase during major life cycle stages, namely, vegetative mycelial stage, dormant sclerotial stage and sexual ascocarps formation stage were determined in Morchella conica, M. angusticeps and M. esculenta. There were significant differences in production of laccase, polyphenol oxidase and peroxidase enzymes not only in different life cycle stages but also amongst putative taxa of the genus Morchella tested. In general, it was observed that the mycelial extracts exhibited less activities of all the seven enzymes and the production of test enzymes was recorded the maximum in dormant sclerotial stage, which later reduced gradually from sclerotial to fruit body maturation stage. Nevertheless, the enzymes were manifold higher in fruitbody than in vegetative mycelial stage. The significant decline in the activities of all the enzymes from sclerotia to fruitbody maturation under present study were related to biochemical activity of these enzyme in bringing about metamorphic changes in sclerotia in primordial initiation and eventually maturation of ascocarp. The study suggests that sexual cycle may be triggered by manipulating enzymatic activities of vegetative sclerotial stage.